Improving the Quality of Learning through Teacher’s Guidance - Fitriana, Fitriana; Harapan, Edi; Kesumawati, Nila (Yayasan Sembilan Pemuda Indonesia, 2021)
This study identified teacher teaching development as a means of improving the quality of learning at SD Negeri 15 Betung. The school served as the site for this study. This is a qualitative in which data is gathered through interviews, observation, and documentation. According to the results, teacher teaching development as an effort to improve the quality of learning at SD Negeri 15 Betung could be said good the ability of teachers to manage classes in terms of lesson plan and learning implementation; and the ability of the teacher to manage classes in terms of the teacher's activities opening and closing lessons. The teacher's competence handle the class means the teacher's activities in delivering reinforcement.